The Function of Primary Slang Used as a Reflection of Friendship in Incoming Movie (2024) - Ni Kadek Friandani; Sang Ayu Isnu Maharani; Ni Made Ayu Widiastuti (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Slang as an informal language variety has an important role in forming and reflecting the social identity of a group. This study discusses the function of primary slang as a reflection of friendship in an American teen comedy movie entitled Incoming released in 2024. This study aims to identify the form  of primary slangs used in the movie and analyze their functions in reflecting social relations between characters. The method used is descriptive qualitative with documentation techniques. Data are analyzed based on the context of conversations between characters in the movie with an emphasis on the social meaning in the use of primary slang based on the theory of Allan & Burridge (2006). Based on seven functions of slang, there are four functions identified in the analysis, consists of:  to initiate relaxed conversation, to adress, to reveal anger, and to show intimacy. Among the four functions, to initiate relaxed conversation is the most dominant function that appears. This shows that slang is widely used to maintain relaxed, familiar, and humorous interactions between friendly characters. On the other hand, the functions to express impressions, to humuliate, and to form intimate atmosphere were not found in the analyzed data.